Maternal and Fetal Outcomes Following Cesarean Section in Comprehensive Emergency Obstetric Care Program at Nuwakot District Hospital - Bhandari, BR (Nepal Journal of Obstetrics and Gynaecology, 2016)
Aims: This study was conducted to assess the fetal and maternal outcomes following cesarean section in Trishuli District Hospital at Nuwakot, Nepal Methods: A hospital based study was conducted in Trishuli District Hospital Nuwakot from 14th March 2012 to 13th March 2013 among 327 pregnant women who underwent cesarean section in Trishuli District Hospital Nuwakot and met the inclusion criteria of this study. Results: The most common indication of caesarean section was (n=139, 42.6%) foetal distress (n=98, 30% moderate to thick meconium stained liquor; n=41, 12.6% foetal tachybradycardia). Among maternal complications, wound infections was seen in seven (2.1%) pregnant women, uterine rupture in two (0.6%), post partum haemorrhage in one (0.3%), post partum eclampsia in one (0.3%) and peurperial pyrexia in one (0.3%). Among perinatal complications, birth asphyxia was present in 10 (3%) neonates, neonatal sepsis in seven (2%) and perinatal death in 12 (3.5%) neonates. Conclusions: Better BEmOC reduced the number of CEmOC requirement. Providing CEmOC in district level is the vital measure in safe motherhood for reducing maternal and perinatal morbidities and mortalities. But for improving maternal and perinatal outcomes in district level, there should be adequate skilled manpower in maternity ward and operation theature, adequate infrastructures in preoperative, operative and postoperative wards, blood bank and neonatal high dependency unit in CEmOC.